DEVELOPMENT OF A MATHEMATICAL MODEL FOR OPTIMIZATION OF TECHNICAL AND OPERATIONAL PARAMETERS OF URBAN ELECTRIC TRANSPORT - Lesnikova, I. Yu.; Khalipova, N. V.; Kuzmenko, A. I.; Razghonov, S. A.; Lesnikov, P. V. (Systems and Technologies, 2023)
The article is intended to improve passenger transportation by urban electric transport. An optimization model has been developed, which allows to optimally distribute the available rolling stock along the city routes, which will allow transporting as many passengers as possible, reducing operating costs and increasing comfort for passengers on trolleybus routes in Dnipro. The efficiency of the implementation of this model is analyzed. The importance of the quality of passenger service increases in the context of the formation of a market environment and the development of competition (between individual modes of transport). With the development of the transport services market, the consumer (passenger) has the opportunity to choose the most high-quality, convenient and safe type of transportation. The passenger will choose the mode of transport where the quality of service (guarantees of politeness, friendliness, comfort, speed, safety, etc.) is the highest. Transport companies selected according to such criteria will have higher incomes, profits, and will be the most competitive. The purpose of the work: development of measures to improve the efficiency of passenger transportation in urban electric transport. In the process of writing the article, the following tasks were performed: statistical data of passenger transportation by urban electric transport in Ukraine and in the city of Dnipro were analyzed; a model of optimal distribution of rolling stock on the routes of urban electric transport has been developed; The optimization problem has been solved and the results of the solution have been analyzed. The developed optimization model makes it possible to optimize the number of rolling stock that carries the available passenger traffic on routes, reduce operating costs and increase the level of comfort for passengers. The main characteristics of some trolleybus routes in the city of Dnipro were also calculated; The main operational characteristics of these routes are calculated, according to which the intervals of movement of trolleybuses, the time of rotation on the route were determined. As a result of the calculation of the optimization model, it was obtained that it is necessary to have 52 units of rolling stock, instead of 56 (by 8%), to increase the average comfort coefficient by 15.7%, to reduce the cost of an hour of work by 3273.7 UAH (8%). It should be noted that the decrease in rolling stock affects the interval of movement of trolleybuses, but this decrease occurs on routes where there is a large number of rolling stock. The interval will increase by an average of 1.5 minutes, which is acceptable for passengers to wait. Measures can also be taken to increase the speed of trolleybuses, for example, the allocation of a lane for public transport on Ave. Slobozhansky.